Altered Neural Correlate of the Self-Agency Experience in First-Episode Schizophrenia-Spectrum Patients: An fMRI Study - Spaniel, Filip; Tintera, Jaroslav; Rydlo, Jan; Ibrahim, Ibrahim; Kasparek, Tomas; Horacek, Jiri; Zaytseva, Yuliya; Matejka, Martin; Fialova, Marketa; Slovakova, Andrea; Mikolas, Pavol; Melicher, Tomas; et al. (Schizophrenia bulletin, 2016)
BACKGROUND: The phenomenology of the clinical symptoms indicates that disturbance of the sense of self be a core marker of schizophrenia. AIMS: To compare neural activity related to the self/other-agency judgment in patients with first-episode schizophrenia-spectrum disorders (FES, n = 35) and healthy controls (HC, n = 35). METHOD: A functional magnetic resonance imaging (fMRI) using motor task with temporal distortion of the visual feedback was employed. A task-related functional connectivity was analyzed with the use of independent component analysis (ICA). RESULTS: (1) During self-agency experience, FES showed a deficit in cortical activation in medial frontal gyrus (BA 10) and posterior cingulate gyrus, (BA 31; P < .05, Family-Wise Error [FWE] corrected). (2) Pooled-sample task-related ICA revealed that the self/other-agency judgment was dependent upon anti-correlated default mode and central-executive networks (DMN/CEN) dynamic switching. This antagonistic mechanism was substantially impaired in FES during the task. DISCUSSION: During self-agency experience, FES demonstrate deficit in engagement of cortical midline structures along with substantial attenuation of anti-correlated DMN/CEN activity underlying normal self/other-agency discriminative processes.
Keywords: dospělí; Magnetic Resonance Imaging; self-agency; Female; Connectome; Psychomotor Performance; independent component analysis; nervová síť; Adult; ženské pohlaví; percepční poruchy; pohybová aktivita; lidé; psychomotorický výkon; Nerve Net; Perceptual Disorders; neuroimaging; magnetická rezonanční tomografie; first-episode schizophrenia; schizofrenie; prefrontální mozková kůra; konektom; Male; cingulární gyrus; Schizophrenia; Motor Activity; mužské pohlaví; fMRI; Gyrus Cinguli; Prefrontal Cortex; Humans